Abundance and Diversity of Microarthropods on Microhabitat of Oil Palm - Wahyuni, Titik Tri; Widyastuti, Rahayu; Santosa, Dwi Andreas (Jurnal Ilmu Tanah dan Lingkungan, 2015)
Acari and Collembola are microarthropods that live in soil and litter layer. In soil ecosystems, microarthropods have a role in organic matter decomposition through their ability to breakdown litter that accelerate the degradation of organic matter. This research aims to study the abundance and diversity of microarthopods at various microhabitats of oil palm. The research consisted of three stages: sampling, extraction and identification of soil fauna. Sampling plot has a dimension of 50 x 50 m which was consisted of 5 points, each point consist of 11 microhabitats. Samples were taken at several microhabitat of oil palm namely soil with distance 0 m; 1m; 3 m from oil palm stand, compost accumulations between the oil palm trees, litter accumulation on the branch at height 30 cm; 90 cm; 150 cm, epiphytes at height 30 cm; 90 cm; 150 cm and branch stub. Samples were taken in January 2014. Extraction of microarthropods was conducted using Kempson Extractor, while identification of microarthropods was done to the subordo level for Acari and the famili level for Collembola. The abundance and diversity of microarthropods were calculated using the formula abundance according to Meyer and Shannon’s diversity index. To know differences of abundance and diversity of microarthropods at various microhabitats were used one way ANOVA and Duncan analysis. The results showed that the higest abundance of Acari found at litter accumulation on the branch and epiphyte. The higest abundance of Acari found at microhabitat of epiphyte with height 30 cm was 4,408 m-2, while the higest abundance of Collembola found at microhabitat of epiphyte with height 30 cm was 6,173 m-2. The diversity of microarthropods at microhabitats of oil palm is based on index Shannon’s diversity. Keywords: Abundance, diversity, microarthropods, microhabitat, oil palm